The Influence of Financial Literacy, Risk Orientation and Qualified Accountants on Performance in Micro, Small and Medium Enterprises: The Mediating Role of Management Accounting - Ahmad, Kamilah (International Review of Management and Marketing, 2024)
There are limited studies examining whether the owner or manager’s financial literacy, risk orientation, and deployment of qualified accounting staff influence the adoption of management accounting practices (MAPs) and performance in the context of micro, small, and medium-sized enterprises (MSMEs). Thus, this study seeks to examine the effect of financial literacy, qualified accounting staff, and risk orientation on performance, with MAPs as a mediating variable within the context of MSMEs from a developing country. A quantitative study was established where a questionnaire survey was administered to Malaysian MSMEs from different sectors. Based on 105 valid responses, the results show that MAPs have positive and significant effect on performance. The study also reveals that MAPs significantly and fully mediate the relationships between owner/manager’s financial literacy, qualified accounting staff, risk orientation, and performance of MSMEs. The findings provide significant data for identifying key factors within the setting of small businesses in developing countries to improve financial resilience in the current competitive economy. Our findings offer valuable insight to practitioners about how competencies and key management accounting concepts can consequently affect the positive outcomes of organisational performance.